Cost of care for hypertension in a selected health center of urban Puducherry: An exploratory cost-of-illness study - Sitanshu Sekhar Kar; Vinoth Kumar Kalidoss; Uma Vasudevan; Shifalika Goenka (International Journal of Noncommunicable Diseases, 2018)
Background: Among noncommunicable diseases, hypertension is one of the most important risk factors, the control of which imposes a huge financial burden on the healthcare system and the society. Objectives: The objective of this study was to measure the monthly cost incurred in care of hypertension in urban Puducherry and to estimate the total annual cost required to provide care for the adults with hypertension in a typical primary health center (PHC) of India. Materials and Methods: The study was conducted in the service area of urban health center (UHC) in Puducherry, functioning under the Department of Preventive and Social Medicine, JIPMER. A sample of 238 adults ≥ 18 years identified through a baseline survey conducted in 2014 was interviewed using a pretested semi-structured questionnaire. The questionnaire collected information on sociodemographic data, place of seeking hypertension care, and its duration and various direct and indirect costs incurred. Recall period was fixed as 1 month for OP care and 1 year for hospitalization. A prevalence-based approach was used for calculating the cost of illness. Average monthly and annual direct and indirect costs were calculated and were compared across the type of facility of care and with the presence or absence of comorbidities. The cost of care from UHC and other government hospitals were calculated from standard rates. The average annual cost from UHC was used to calculate the annual amount required to provide care of hypertension in a typical PHC of India. Results: Among the 238 participants, 73.5% (n = 175) were female, and the mean (standard deviation) age was 58 (11.7) years. Majority (72%, n = 172) took care for their hypertension from UHC, JIPMER. Half of them (n = 119) had associated comorbidities. Average monthly direct cost of care for hypertension was 223.2 (198.0–329.4) Indian national rupees. There was statistically significant difference in the cost of care among participants utilizing public and private facilities, and also among participants with comorbidities and without comorbidities. The estimation of annual cost of hypertension care for a typical PHC comes around 1.07 crores. Conclusion: The control of hypertension in a community leads to a significant load on health system; however, it is essential for preventing further catastrophic costs as a result of complications and mortality. This cost could be saved if we could prevent the population from becoming hypertensives by preventive measures, and it will further lead to reduction in mortality and morbidity and the associated costs.